(In)Sécurités foncières en Afrique. Débat global et enjeux locaux - (:unkn) unknown (My University, 2011)
Land (In)Securities in Africa. Global Debate and Local Issues - In 2008, the NGO Grain pulled the alarm cord on the acceleration of "land grabbing" by foreign investors in South countries, most particularly in Africa (Grain 2008). Following the footsteps of this report, several NGOs had denounced the poor financial compensation required in exchange for emphyteutic leases, the fiscal advantages offered to foreign investors, and the risks of the breakdown of food-producing agriculture. Emphasized by the global food crisis of 2008, the extent and consequences of these foreign land investments, presented by the media as a devastating trend, have since been put into perspective.
Keywords: African Research